The Impact of Capacity Cost Rate and Time Equation of Time-Driven Activity-Based Costing (TDABC) on Electric Component - Nurul Farahin, Zamrud; Mohd Yazid, Abu; Nik Nurharyantie, Nik Mohd Kamil; Filzah Lina, Mohd Safeiee (Springer, 2020)
Today, in this big business competition, it is important for the company to incorporate an accurate cost estimation to decide the best price for products to gain profits. This research study revolves around a case study company, which manufactures electric and electronics products. The objective of this study is to analyze the manufacturing process cost at the case study company using Time-Driven Activity-Based Costing (TDABC). This research began by collecting data related to the production costs of a selected product. The product has been selected based on the volume of production which is high and continuous production. There are two parameters of TDABC to be considered. Firstly, the capacity cost rate and secondly, the time required to perform activities. Both parameters can be estimated easily and objectively. Eventually, the results showed that by applying the TDABC method, the capacity utilization and time efficiency can be clearly viewed. The company gained information on manufacturing costs and time utilization for those activities and could generate further action to increase efficiency and have the opportunity to use this method to enhance the accuracy in determining the appropriate process for any kind of product.